ҚАРАҚАЛПАҚ ХАЛЫҚ ДӘСТАНЫ «ШАРЬЯР» - ЭСТЕТИКАЛЫҚ ТӘРБИЯ ҚУРАЛЫ СЫПАТЫНДА - Алламбергенов, Е.К. (FAN va JAMIYAT, 2019)
The article deals with one of the important issues of pedagogy-aesthetic education. Its content and essence, its relationship with other types of education is analysed in the examples taken from the karakalpak national epos “Shariyar”. The author proves that the epos “Shariyar” with its literary images, as well as other works of folklore and written literature is a tool in developing aesthetic outlook of young people.